Assessing the prefrontal functional connectivity using wavelet coherence analysis of oxygenation signals - Qingyu Han; Yuanjin Gao; Wenhao Li; Zengyong Li; Qing Xin (Proceedings of the International Conference on Biomedical Engineering and Informatics, 2014)
This study aims to assess the prefrontal functional connectivity using wavelet coherence analysis of cerebral tissue oxyhaemoglobin concentrations (Delta [HbO 2 ]) signals in subjects with cerebral infarction(CI) during the resting state. Continuous recordings of near-infrared spectroscopy (NIRS) signals were gained from the right and left prefrontal lobe in 15 elderly subjects with CI (age: 75.1 ± 9.2 years) and 18 healthy elderly subjects (age: 69.9 ± 7.3 years) during the resting state. The coherence between right and left prefrontal lobe Delta [HbO 2 ] oscillations in 4 frequency intervals (I, 0.6-2 Hz; II, 0.145-0.6 Hz; III, 0.0520.145 Hz; IV, 0.021-0.052 Hz) was analyzed by the wavelet coherence analysis. In healthy subjects, the Delta [HbO 2 ] were significantly wavelet coherent in interval I (0.6-2 Hz) and III (0.052-0.145 Hz) (p<;0.05). In elderly subjects with CI, the left and right Delta [HbO 2 ] were significantly wavelet coherent in interval I (0.6-2 Hz) (p<;0.05). The wavelet coherence was significantly lower in interval II (F=6.658, p=0.014), III (F=18.164, p=0.000) and IV (F=4.295, p=0.046). The difference using the wavelet coherence of the CI subjects and the healthy subjects demonstrates an vary cerebral autoregulation caused by CI. This research gives a original insight into the dynamics of Delta [HbO 2 ] oscillations. This method may be beneficial in detecting the risk for alter cerebral autoregulation. This might indicate a damaged brain functional connectivity due to CI in the subjects.